Growth and survival of Blue Swimming crab (portunus pelagicus) reared on frozen and artificial foods - Mhd, Ikhwanuddin; Mohamad, N. Azra; Yeong, Yik Sung; Abol-Munafi, Ambok Bolong; Shabdin, Mohd Long (Scientific Research, 2013)
Experiments were conducted to evaluate the efficacy of two frozen organism (with and without instant Nannochloropsis oculata and with and without instant encapsulated Spirulina) and artificial diet (with and without artificial encapsulated shrimp larvae feed) with live food as continues feed in the larval rearing of blue swimming crab, Portunus pelagicus. The larvae were conducted with six treatments and each treatment with three replications on newly one day hatched larvae in each replication. Results showed that these larvae fed with a combination diet of instant frozen N. oculata, Artemia nauplii and rotifer give a higher survival rate till 1st day juvenile crab compared to the treatment with instant encapsulated Spirulina and artificial diet (with artificial encapsulated shrimp larvae feed). One of experiments treated with encapsulated Spirulina recorded only 16 days for the zoea to reach the C1, one day earlier as compared to previous trials treated with and without instant frozen N. oculata. One of the experiments treated with artificial encapsulated shrimp larvae feed recorded 18 days for the zoea to reach the C1, 1 to 2 days longer as compared to all the previous trials earlier. Food type influenced survival, development, and metamorphosis to megalopa and 1st day juvenile crab of P. pelagicus zoea larvae. Our findings illustrate that the best survival, the most rapid development and the highest number of 1st day juvenile crabs were obtained from larvae fed with a combination diet of frozen N. oculata, Artemia nauplii and rotifer from hatching till the 1st day juvenile crab.